2021
DOI: 10.3390/nano11020457
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Polyester Nanofibrous Membrane with a Fibrin-Platelet Lysate Coating on Keratinocytes and Endothelial Cells in a Co-Culture System

Abstract: Chronic wounds affect millions of patients worldwide, and it is estimated that this number will increase steadily in the future due to population ageing. The research of new therapeutic approaches to wound healing includes the development of nanofibrous meshes and the use of platelet lysate (PL) to stimulate skin regeneration. This study considers a combination of a degradable electrospun nanofibrous blend of poly(L-lactide-co-ε-caprolactone) and poly(ε-caprolactone) (PLCL/PCL) membranes (NF) and fibrin loaded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 53 publications
2
24
0
Order By: Relevance
“… 14 , 15 The fibrin coating was also shown to serve as an excellent substrate for cell growth on PLA nanofibers 16 and on PLCL/PCL nanofibrous membranes. 17 We previously reported that NF with fibrin containing 20% of hPL enhanced proliferation and differentiation of human keratinocytes. 17 However, the rather low activity of incorporated growth factors from the hPL reduced the overall effect.…”
Section: Introductionmentioning
confidence: 93%
“… 14 , 15 The fibrin coating was also shown to serve as an excellent substrate for cell growth on PLA nanofibers 16 and on PLCL/PCL nanofibrous membranes. 17 We previously reported that NF with fibrin containing 20% of hPL enhanced proliferation and differentiation of human keratinocytes. 17 However, the rather low activity of incorporated growth factors from the hPL reduced the overall effect.…”
Section: Introductionmentioning
confidence: 93%
“…Nanofibers based on PBSu [ 15 ], PLCL/PCL [ 163 ], PLA/Hypericum perforatum oil (HPO) [ 21 ], PLA/GO/Q [ 162 ], PLA/silver (I)-diclofenac complex with (2-methylimidazole) [ 168 ], and PBAT/PCL [ 22 ] are few examples of polyester-based materials successfully obtained via the electrospinning method.…”
Section: Wound Dressingsmentioning
confidence: 99%
“…The most common solvent mixtures used are chloroform:methanol, chloroform:ethanol, and dichloromethane (DCM):methanol at 90:10, 80:20, and 70:30 solvent ratios, respectively, for electrospinning of PBSu/food-grade agents [ 15 ]; DCM/N, N-dimethylformamide (DMF) at a ratio of 1:9 to obtain PLA/graphene oxide (GO)/quercetin (Q) electrospun scaffolds [ 162 ]; and DCM/DMF (7:3, v / v ) and 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP)/ethanol (7:3, v / v ) for preparing encapsulated antimicrobial agents in PLA/PEO/PVP matrices [ 16 ]. The addition of acetic acid to the mixture of chloroform:ethanol to dissolve the PLCL/PCL copolymer prevented the formation of beads, and led to fibers with diameters in the range of 200 nm to 2.8 µm [ 163 ]. There were also reported nanofibers with diameters of 1.68 ± 0.58 µm and 1.51 ± 0.64 µm in the case of electrospun PLA/HPO [ 21 ], 1.107–1.243 µm in the case of PLA/GO/Q [ 162 ], and 1.9 ± 0.5 μm in the case of PHB/PCL modified with hybrid melanin–TiO 2 nanostructures [ 18 ], which are considered as adequate for cell adhesion and attachment.…”
Section: Wound Dressingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A platelet concentrate was prepared via the centrifuge separation of platelets from human buffy coats obtained from 4 patients. The experimental procedure was previously described by Blanquer et al [7]. Briefly, the buffy coats from the 4 patients were mixed and centrifuged to separate the platelet concentrate from the red blood cells and leukocytes.…”
Section: Platelet Lysate Preparationmentioning
confidence: 99%